2017
DOI: 10.3758/s13414-017-1311-z
|View full text |Cite
|
Sign up to set email alerts
|

Limited evidence of individual differences in holistic processing in different versions of the part-whole paradigm

Abstract: The part-whole paradigm was one of the first measures of holistic processing and it has been used to address several topics in face recognition, including its development, other-race effects, and more recently, whether holistic processing is correlated with face recognition ability. However the task was not designed to measure individual differences and it has produced measurements with low reliability. We created a new holistic processing test designed to measure individual differences based on the part-whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
24
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 48 publications
7
24
1
Order By: Relevance
“…Together, these studies suggest that holistic processing is not necessary to activate perceptual memories of the facial identity of familiar faces, which is consistent with behavioral work suggesting that holistic processing is not strongly correlated with face recognition abilities (Konar et al , 2009 ; Wang et al , 2012 ; DeGutis et al , 2013 ; Richler et al , 2015 , but see Rezlescu et al , 2017 ; Sunday et al , 2017 ).…”
Section: Discussionsupporting
confidence: 79%
“…Together, these studies suggest that holistic processing is not necessary to activate perceptual memories of the facial identity of familiar faces, which is consistent with behavioral work suggesting that holistic processing is not strongly correlated with face recognition abilities (Konar et al , 2009 ; Wang et al , 2012 ; DeGutis et al , 2013 ; Richler et al , 2015 , but see Rezlescu et al , 2017 ; Sunday et al , 2017 ).…”
Section: Discussionsupporting
confidence: 79%
“…Together, these studies suggest that holistic processing is not necessary to activate perceptual memories of facial identity of familiar faces, which is consistent with behavioral work suggesting that holistic processing is not strongly correlated with face recognition abilities (Konar, Bennett, & Sekuler, 2009;Rezlescu, Susilo, Wilmer, & Caramazza, 2017;Richler, Floyd, & Gauthier, 2015;Sunday, Richler, & Gauthier, 2017, but see DeGutis, Wilmer, Mercado, & Cohan, 2013Wang, Li, Fang, Tian, & Liu, 2012).…”
Section: Is Holistic Processing Necessary For Facial Recognition?supporting
confidence: 81%
“…Findings have, however, been rather inconsistent. Whether this is due to poor reliability of the measures used (DeGutis et al, 2013;Ross et al, 2015;Sunday et al, 2017;Wang et al, 2012), inefficient control of the variables that may have driven observed effects (Richler et al, 2015), uncertainty regarding whether the measures employed tap the same construct (Rezlescu et al, 2017;Wang et al, 2012), or a combination is unclear. Still, an individual difference approach to visual cognition seems to be a valuable and also necessary complement to studies examining dissociations (Wilmer, 2008) as it can reveal domain-general operations.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the results from these studies have been rather inconsistent. Some studies have reported positive findings (DeGutis, Wilmer, Mercado, & Cohan, 2013;Richler, Cheung, & Gauthier, 2011;Wang, Li, Fang, Tian, & Liu, 2012), whereas others have not (Konar, Bennett, & Sekuler, 2010;Richler, Floyd, & Gauthier, 2015;Sunday, Richler, & Gauthier, 2017). Although some studies suggest that these measures of holistic processing tap the same process (DeGutis et al, 2013), other studies have failed to find a correlation between them (Rezlescu, Susilo, Wilmer, & Caramazza, 2017;Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%